The Effects of Genocide on Tourism Industry in Bugesera District in Rwanda. - Egide, Mudaheranwa (Kabale University, 2019)
Research Report Submitted in Partial Fulfillment of the Requirement for the award Of Bachelor’s Degree in Tourism Management of Kabale University